Coaching English for Young Learners through Deep Learning at PPA IO-0133 Krammer Hilina’a - Zega, Riswan; Tel, Kristof M E; Laoli, Jacqueline; Gulo, Neni S; Tel, Silvan H; Maru’ao, Fincessia F; Harefa, Ryan M (Jurnal Pengabdian Masyarakat Bhinneka, 2026)
English proficiency for Young Learners (EYL) plays a crucial role as a basic foundation for fostering learning motivation. However, preliminary observations at PPA IO-0133 KrammerHilina'a revealed minimal student abilities, with only 17% of students meeting the initial competency targets. This Community Service (PKM) program aims to strengthen basic English skills through a Deep Learning approach. The activities were conducted in seven systematic stages, integrating techniques such as role play, games, imitation, singing, and coaching strategies. The results showed a consistent positive improvement trend in each session, with an overall average competency increase of 65%. In the final evaluation stage, 96% of students successfully achieved the competency set targets, with an average score increase of 55 points. In conclusion, the integration of technology and modern pedagogy is effective in creating a strong, interactive, and sustainable English language foundation for children at PPA IO-0133 Krammer Hilina'a.